2014
DOI: 10.4110/in.2014.14.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Serum Levels of Interleukin-17 and Interleukin-18 in Normal Pregnancy

Abstract: We performed this study to evaluate the role of Interleukin-17 (IL-17) and Interleukin-18 (IL-18) in insulin resistance during normal pregnancy. This descriptive cross sectional study was carried out on 97 healthy pregnant women including 32, 25, and 40 individuals in the first, second, and third trimesters, respectively, and on 28 healthy non pregnant women between the autumn of 2012 and the spring of 2013. We analyzed the serum concentrations of IL-17 and IL-18 by using the enzyme linked immunosorbent assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…During normal pregnancy, Th2 cytokines are predominant, but a progressive shift toward Th1 cytokines, which reinforces the role of Th17 cytokines, occurs by the end of gestation . Serum interleukin‐17 levels in pregnant women are significantly higher than in nonpregnant women and ascend especially in a late gestation . In our case, histopathological analysis of the placenta after delivery revealed massive neutrophilic infiltrate compatible with chorioamnionitis.…”
supporting
confidence: 60%
“…During normal pregnancy, Th2 cytokines are predominant, but a progressive shift toward Th1 cytokines, which reinforces the role of Th17 cytokines, occurs by the end of gestation . Serum interleukin‐17 levels in pregnant women are significantly higher than in nonpregnant women and ascend especially in a late gestation . In our case, histopathological analysis of the placenta after delivery revealed massive neutrophilic infiltrate compatible with chorioamnionitis.…”
supporting
confidence: 60%
“…These results indicate that high level of serum IFN-γ might contribute to the decreases in blood glucose and triglyceride levels. However, according to a recent report, IL-17 appeared to have no effect on glucose and lipid metabolism (47). These studies suggest that the decrease in the prevalence of IFG and hypertriglyceridemia associated with elevated serum TgAb may also result from the increased IFN-γ secretion in the pathogenesis of AIT.…”
Section: Referencesmentioning
confidence: 84%
“…Pregnancy is accompanied by insulin resistance and glucose metabolism disorders. There is a progressive augmentation during the gestation course in the maternal insulin secretary response to glucose and a variety of other stimulations ( 40 , 41 ). Data from this systematic review indicated that DHA-enriched fish oil (800 mg/d) has no effect on the prevention of GDM.…”
Section: Discussionmentioning
confidence: 99%